Indigenous Mothers' Aspirations for Their Children in Perth, Western Australia: The Value of Education and Schooling. Issue 1 (22nd January 2009) - Lette, Helen; Tursan d'Espaignet, Edouard; Slack-Smith, Linda; Hunt, Kerry; Nannup, Janine
Abstract: This project involved the collection of stories about the aspirations, goals and strategies from a sample of mothers of Indigenous children living in Perth, Western Australia. Analysis of the semi-structured interviews indicated that the education of their children was important for many of the mothers. Whilst some of the mothers preferred their children to learn about their Indigenous history, culture and identity, others valued the type of education that emanates from a mainstream-style school system. A major theme was a need for schools to partner with Indigenous parents in the decision-making process to engage the families in a positive education experience.